1992
DOI: 10.1088/0022-3727/25/2/014
|View full text |Cite
|
Sign up to set email alerts
|

Electron energy distribution functions in weakly ionized argon

Abstract: The authors present measurements of the electron energy distribution functions (EEDF) for electrons in argon discharges at moderate and high E/N values (E being the electric field and N the gas density), for homogeneous electric fields and a low-current diffuse glow regime. Results were obtained for electric field to gas density ratios (E/N) from 500 Td to 50 kTd (1 Td=10-21 V m2). A multigrid energy analyser with a retarding grid potential was used to measure distribution functions of electrons sampled throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The development of run-away electrons has been studied in a range of constant uniform electric fields with particle swarm experiments [76,24,111,70,14,15], in agreement with [112,10], where it was shown that thermal electrons run away when electric field exceeds a critical strength of E≈ 260 kV/cm at standard temperature and pressure, and the runaway rate increases as the field increases. This is quite reasonable if one considers that in such a field an electron gains 200 eV within less than 8µm, which is the range of the mean free ionization length.…”
Section: Physical Predictionsmentioning
confidence: 59%
See 1 more Smart Citation
“…The development of run-away electrons has been studied in a range of constant uniform electric fields with particle swarm experiments [76,24,111,70,14,15], in agreement with [112,10], where it was shown that thermal electrons run away when electric field exceeds a critical strength of E≈ 260 kV/cm at standard temperature and pressure, and the runaway rate increases as the field increases. This is quite reasonable if one considers that in such a field an electron gains 200 eV within less than 8µm, which is the range of the mean free ionization length.…”
Section: Physical Predictionsmentioning
confidence: 59%
“…In particular, individual electrons can run away [10,11,12]. And when the electric field exceeds a threshold, the majority of electrons will run away and the density or fluid model will break down completely [13,14,15].…”
Section: High Electron Energies and Electron Run-awaymentioning
confidence: 99%
“…2. The configuration of the discharge cell is similar to that used in earlier work [50]. It consisted of two parallel circular stainless-steel electrodes 4.2 cm in diameter separated by a distance of 1.4 cm.…”
Section: Methodsmentioning
confidence: 99%
“…For conventional breakdown, E thr is proportional to the number density of molecules. This kind of electric discharge, or breakdown, has been extensively studied and well documented [2][3][4][5]. In air at atmospheric pressure, E thr ∼ 2 MV m −1 .…”
Section: Introductionmentioning
confidence: 99%